Dari Tradisi Ke Masa Depan: Tantangan Pendidikan Islam dalam Masyarakat Kontemporer - Ridwan, Mohammad; Maryati, Sulis (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
This article aims to explore the challenges faced by Islamic education in the context of an ever-changing contemporary society. By highlighting the transition from tradition towards the future, this article identifies the main obstacles encountered by the Islamic education system and explores innovative efforts to overcome these challenges. The research method employs a qualitative approach, specifically library research, to analyze various relevant literature sources. The discussion results show that Islamic education faces various issues, ranging from conceptual-theoretical to operational-practical aspects. However, by integrating traditional values with modern advancements, Islamic education can remain relevant and make a significant contribution to shaping a generation that is strong in faith and ready to face the dynamics of changing times. The utilization of technology in learning, the development of ethics and empathy through character education, and the integration of Islamic values in a contemporary context are some practical efforts identified as innovative solutions. The main contribution of this article is the emphasis on the importance of renewing Islamic education to remain relevant in addressing the social, technological, and value changes in contemporary society.